2008
DOI: 10.1667/rr1359.1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane is a More Sensitive Target than Cytoplasm to Dense Ionization Produced by Auger Electrons

Abstract: To improve radioimmunotherapy with Auger electron emitters, we assessed whether the biological efficiency of (125)I varied according to its localization. A-431 and SK-OV-3 carcinoma cells were incubated with increasing activities (0-4 MBq/ml) of (125)I-labeled vectors targeting the cell membrane, the cytoplasm or the nucleus. We then measured cell survival by clonogenic assay and the mean radiation dose to the nucleus by assessing the cellular medical internal radiation dose (MIRD). The relationship between su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 28 publications
4
89
1
1
Order By: Relevance
“…Several strategies have been proposed to optimally localize the radionuclides with respect to the sensitive targets in cells (5,10,11). However, recent observations suggest that nuclear accumulation may not be required in order for an Auger electron-emitter to produce the high-LET type of radiotoxicity (12). In contrast, radionuclides bound outside the cell nucleus (e.g., in the cytoplasm), on the cellular membrane, or extracellularly do not produce severe lethal effects and have a relative biological effectiveness comparable to that observed for low-LET radiation (13).…”
mentioning
confidence: 99%
“…Several strategies have been proposed to optimally localize the radionuclides with respect to the sensitive targets in cells (5,10,11). However, recent observations suggest that nuclear accumulation may not be required in order for an Auger electron-emitter to produce the high-LET type of radiotoxicity (12). In contrast, radionuclides bound outside the cell nucleus (e.g., in the cytoplasm), on the cellular membrane, or extracellularly do not produce severe lethal effects and have a relative biological effectiveness comparable to that observed for low-LET radiation (13).…”
mentioning
confidence: 99%
“…One alternative could be the use of short-range particles such as a-emitters (21) or Auger electron emitters. We previously showed that anti-carcinoembryonic antigen (CEA) mAbs labeled with Auger electron emitters and intravenously injected into mice xenografted with cancer cells could significantly delay the growth of small peritoneal solid tumors (7,23). We thus wanted to assess the efficiency and toxicity of 125 I-mAb when used in IP RIT for mice bearing small peritoneal tumors.…”
mentioning
confidence: 99%
“…33 The energy of Auger electrons is about 20-50 keV and can travel up to 2-500 nm in tissues. The cytotoxic effects of a-particles and Auger electrons are attributed to their ability to induce DNA damage.…”
Section: Optimal Radionuclides and Antibody Characteristics For Intramentioning
confidence: 99%
“…However, previous in vitro studies from the group demonstrated that in comparison to internalizing radioimmunoconjugates, noninternalizing 125 I-labeled antibodies exhibited more pronounced cell death suggesting the sensitivity of the cell membrane to ionizing radiation. 33 Subsequently, the therapeutic superiority of noninternalizing 125 I-labeled antibodies in treating peritoneal carcinomatosis was demonstrated in vivo using the vulvar squamous carcinoma xenograft model. 20 After intravenous administration, the maximal tumor accretion of 125 I-labeled noninternalizing anti-CEA MAb 35A7 was significantly higher than radioiodinated internalizing anti-EGFR MAb m225.…”
Section: Optimal Radionuclides and Antibody Characteristics For Intramentioning
confidence: 99%